Dairy potential of Bunaji (White Fulani) and Bokoloji (Sokoto Gudali) breeds - Johnson, A.O.; Buvanendran, V.; Oyejola, B.A. (1984)
The performance of Bunaji and Bokoloji cattle under same management for three years were investigated. Lactation and reproductive data of 888 calvings from both breeds were analysed. Milk yield was significantly different between the breeds. Lactation lengths were also significantly different. Milk yield increased with parity in both breeds, especially in the Bokoloji. The overall calving interval for the two breeds was 365 days and did not differ between breeds. Parity had a significant effect on calving interval, the first calving interval after the first parity being longer by about 18 days than later parities.